The use of a predictive model of postoperative complications and a protocol for assessing the effectiveness of anesthesia in reconstructive and aesthetic surgical interventions on the mammary glands - Sazhyn , Dmytro; Kuchyn, Iurii (The Ukrainian Scientific Medical Youth Journal, 2022)
When developing recommendations for choosing a method of anesthesia for reconstructive and aesthetic surgical interventions on the mammary glands, it is important to evaluate the effectiveness and safety of anesthetic management. In addition to the effect on the central nervous system, general anesthesia has a complex effect on the body, including causing changes in various parts of the metabolism. Metabolic changes associated with surgical stress include activation of catabolic processes and increased proteolysis. The aim of this work was to develop a model for assessing the effectiveness of anesthesia during reconstructive and aesthetic surgical interventions on the mammary glands, as well as to develop an appropriate protocol. The work carried out a step-by-step assessment of the effectiveness of anesthetic management in reconstructive operations on the mammary glands. The performance evaluation tool for creating a predictive risk model in our work was a categorical analysis of the frequency of surgical complications, as well as hemodynamic and metabolic changes, depending on the physical status of patients with ASA. To create a predictive risk model, we used a binary logistic regression method using the SPSS special-purpose package. The probability of postoperative complications was taken as a dichotomous variable in accordance with independent variables. Among the independent variables, the model included such numerical parameters as age, body mass index, glucose, creatinine, intraoperative BIS, intraoperative systolic blood pressure, duration of intervention, pain syndrome 24 hours after the intervention, cognitive impairment 24 hours after the intervention. Among the categorical variables, the type of anesthesia, the class of the patient according to ASA were selected. In the proposed protocol for assessing the effectiveness of anesthesia during reconstructive and aesthetic surgical interventions on the mammary glands, when the threshold sum of coefficients is reached, a risk group is determined using a scale. The sum of prognostic coefficients is equal to or lower than -19.8, the risk is minimal; greater than -19.8 and less than 19.8, the risk is uncertain; if equal to or higher than 19.8, the risk is high. The sensitivity of the protocol was 95.7%, specificity - 93.5%, positive predictive value - 91.8%, negative predictive value - 92.9%. Factor analysis of clinical, anamnestic, instrumental and laboratory parameters in patients who underwent reconstructive and aesthetic surgical interventions on the mammary glands made it possible to establish groups of factors that determine the variability of signs. The developed protocol for assessing the effectiveness of anesthesia during reconstructive and aesthetic surgical interventions on the mammary glands is characterized by parameters of clinical value sufficient for the anesthetic support of reconstructive and aesthetic surgical interventions on the mammary glands.